NEW ASPECTS OF THE CLINICAL COURSE OF CHRONIC BRUCELLOSIS - Maxtob Alimovna Farmanova (World Scientific Research Journal, 2025)
The purpose of this work was to study the clinical and diagnostic features of the course of chronic forms of brucellosis. Material and research methods. We conducted a clinical diagnostic examination of 60 patients with chronic brucellosis who were hospitalized. Results and its discussion. The issue of great theoretical and practical importance is the study of the clinical status of the adult organism of patients with brucellosis in the age aspect. Among the patients with chronic brucellosis examined by us, in 54 (90.0%) patients, the disease began chronically (gradual onset in 10.0%) with high fever in 56 (93.3%), accompanied by chills in 54 (90.0%) and sweating 56 (93.3%). 52 (86.6%) patients also had headaches and weakness. When the infection was generalized against the background of high temperature, the knee, ankle (35%) and relatively rarely hip (5%) joints, as well as the cervical spine (1%) were more often affected.